Strategic Management in Achieving Service Standards at the Center for Community Learning Activities (PKBM) - Mutiara, Diah; Koesmawan, Masyitoh (Asian Journal of Contemporary Education, 2020)
This study aims to analyze the achievement of service standard at the Center for Community Learning Activities (PKBM). The focus of this research is: (1) What is the Community Learning Center formulation strategy in improving service quality? (2) What is the Community Learning Center implementation strategy in improving service quality? (3) What is the Community Learning Center strategy in improving service quality? In this study, the researcher used a qualitative approach with a case study design. Data collection is done by interview, observation, and documentation. Data were analyzed using data reduction techniques, followed by data presentation, and concluding. The results of research at Community Learning Center MitraBuruh Nusantara are through strategic management, Community Learning Center can improve the quality of learning services by expanding outreach not only with workers or factory employees but also with students at school age. The results of research in Community Learning Center Negeri 35 are through strategic management Community Learning Center Negeri 35 can improve the service quality through developing supporting facilities that continue to develop, develop learning plus life skills and skills so that it directly reaches two Community Learning Center service functions namely the learning function and the community empowerment function. The results of research at Faradika’s Community Learning Center are through Faradika’s Community Learning Center strategic management that can improve service quality by developing other programs besides Package A, B, C programs such as reading parks, homeschooling, and unstructured skills courses.